Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2018 International Conference on Transportation &Amp; Logistics, Information &Amp; Communication, Smart City 2018
DOI: 10.2991/tlicsc-18.2018.61
|View full text |Cite
|
Sign up to set email alerts
|

Analyses and Improvement Options on Road Safety Issues in Beijing

Abstract: This paper analyzes the reasons that affect the road safety in Beijing from three aspects: motor vehicles, non-motor vehicles (represented by bicycle) and pedestrians. In view of the above problems, this paper puts forward corresponding improvement points. First, the relevant departments should improve laws and regulations to regulate people's behavior. Second, Increasing the number of the bicycle path is the first and most important step for solving bicycle safety problem. Finally, it is suggested to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some scholars argue that when determining copyright infringement in information network transmission, we should adhere to the principle of technological neutrality, setting aside technical nuances and focusing on the core issues. Otherwise, we may unintentionally deviate from technological neutrality [10]. Others believe that the determination of infringement should be based on technical principles to ensure the protection of the development of the internet industry [11].…”
Section: The Heightened Demands Imposed By the Rapid Development Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars argue that when determining copyright infringement in information network transmission, we should adhere to the principle of technological neutrality, setting aside technical nuances and focusing on the core issues. Otherwise, we may unintentionally deviate from technological neutrality [10]. Others believe that the determination of infringement should be based on technical principles to ensure the protection of the development of the internet industry [11].…”
Section: The Heightened Demands Imposed By the Rapid Development Of T...mentioning
confidence: 99%
“…In the midst of the chaos surrounding information network transmission rights, some scholars argue that researchers or judges should utilize existing legal provisions, including civil law and procedural law governing general legal affairs, when handling disputes related to information network transmission rights. It is not advisable to limit one's perspective to narrow legal provisions, as this may lead to a restrictive legal interpretation and an increasingly narrow path of legal application [12].…”
Section: Mechanical Application Of Server Standardmentioning
confidence: 99%
“…Ou et al studied the driving characteristics of mopeds at signalised intersections and proposed a set of rules for the use of public mopeds to ensure safety [28]. Liu et al found that improving the awareness of traffic safety issues among cyclists is one of the most important ways to solve traffic accident problems [29].…”
Section: Introductionmentioning
confidence: 99%